El Nino is predicted to return in 2023, and experts warn of record-breaking temperatures - Azizul Helmi, Sofian (2023)
El Nino is a weather phenomenon characterised by the warming of the Pacific Ocean near the equator. It can have significant impacts on weather patterns around the world, leading to increased precipitation in some areas and drought in others. The National Oceanic and Atmospheric Administration (NOAA) has predicted that a weak El Nino event is likely to occur in 2023, but it is difficult to say for certain what the exact impacts of this event will be or whether it will cause record-breaking temperatures. It is important to note that El Nino is just one of many factors that can influence global weather patterns, and its effects can vary widely from year to year.